PEMBERIAN ANTISEPTIK PHMB (POLYHEXAMTHYLENE BIGUANIDE) DENGAN RESIKO INFEKSI PADA PENDERITA ULKUS DIABETES MELLITUS - Aryanti, Ayu Sri; Hamdani, Dadi (Jurnal Sahabat Keperawatan, 2025)
Background: Diabetic foot ulcers are a serious complication of Diabetes Mellitus (DM) that carry a high risk of infection Chronic hyperglycemia impairs the immune system, making wound healing slow and increasing susceptibility to microbial invasion An effective wound care strategy is essential to reduce the risk of complications One of the innovations used in wound treatment is the application of Polyhexamethylene Biguanide (PHMB), an antiseptic agent with strong antimicrobial properties that promotes tissue regeneration and infection control Objective: To evaluate the effectiveness of PHMB application in reducing infection risk and enhancing wound healing in patients with diabetic foot ulcers. Method: Case studies using a nursing care approach using descriptive methods include assessment, diagnosis, intervention, implementation, evaluation, and documentation. Data were collected through participatory observation, interviews, literature studies, and supporting examinations of patients with diabetic ulcers. Results: The use of dressings containing PHMB has been proven to reduce the amount of exudate, accelerate the process of tissue granulation, reduce pain, and significantly reduce the area of ​​the wound. After 2 treatments, the results of the wound assessment by Bettes Jensen showed a decrease from 32 to 30. Conclusion: Providing PHMB antiseptic is a diabetic ulcer treatment, can prevent the risk of infection, and accelerate the granulation process of new tissue